1961
DOI: 10.1177/000348946107000310
|View full text |Cite
|
Sign up to set email alerts
|

LVII Circulation of the Inner Ear Fluids

Abstract: Corti, in 18 51, 1 described the cells of the stria vascularis and sug gested that they might be the structure for secreting endolymph. Also in 1851 Reissner 2 described the membrane which now bears his name and divides the scala vestibuli from the scala media, showing anatomically that the membranous labyrinth is a closed system. Fol lowing this observation there has been much speculation concerning the characteristics of the endolymphatic and perilymphatic fluids. In 1927 Stacy Guild 3 performed an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
3

Year Published

1966
1966
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 9 publications
1
16
0
3
Order By: Relevance
“…Volume uptake into endolymph. In classical texts, it was suggested that endolymph was generated by Bradial flow^involving volume and water movements across Reissner's membrane (Naftalin and Harrison 1958;Lawrence et al 1961). In view of extremely low measured endolymph flow rates (0.36 nL/min mean rate toward the base) , it is now generally accepted that endolymph is not secreted in volume.…”
Section: Discussionmentioning
confidence: 99%
“…Volume uptake into endolymph. In classical texts, it was suggested that endolymph was generated by Bradial flow^involving volume and water movements across Reissner's membrane (Naftalin and Harrison 1958;Lawrence et al 1961). In view of extremely low measured endolymph flow rates (0.36 nL/min mean rate toward the base) , it is now generally accepted that endolymph is not secreted in volume.…”
Section: Discussionmentioning
confidence: 99%
“…The first detailed experimental investigation was by He postulated that endolymph is formed by the stria vascularis of the cochlear duct and absorbed in the endolymphatic sac. This theory was supported by the following investigators ( Yamakawa, 1929;Anderson, 1948;Engstrom and Hjorth, 1950), while others believed that endolymph is absorbed elsewhere (Altmann and Waltner, 1950;Lawrence et al, 1961;Rauch et al, 1963). The presumptive importance of the endolymphatic sac in Meniere's disease has also been discussed (Portmann, G., 1927, Portmann, M., 1964House, 1962).…”
mentioning
confidence: 91%
“…This assumption is based on von Bekesy's observation that a fistula in Reissner's membrane rapidly changed the appearance of the under lying hair cells and that they soon ceased functioning. Other workers (4,(12)(13)(14)26) extended these experiments with the purpose of finding out if this hair cell damage could be widened to adjacent regions. The results were always the same, the damage was limited to the immediately underlying hair cells.…”
mentioning
confidence: 99%